Iliopsoas fibrosis after revision of total hip arthroplasty revealed by 68Ga-FAPI PET/CT: a case report - Wang, Yiqun; Sun, Yabing; Song, Junlei; Zhang, Xiaojun; Li, La; Shen, Zhihui; Tian, Jiahe; Ao, Yingfang (Frontiers in Medicine, 2024)
Total hip arthroplasty (THA) is a well-established surgical procedure that has been extensively validated to alleviate pain, enhance joint function, improve the ability to perform daily activities, and enhance overall quality of life. However, this procedure is associated with certain complications, among which skeletal muscle fibrosis is a frequently overlooked but significant complication that can lead to persistent pain.Currently, there is no effective method for diagnosing skeletal muscle fibrosis following total hip arthroplasty.We report a 75-year-old male patient who complained of left groin pain after revision total hip arthroplasty. Serological examinations, X-rays, and bone scan results were all normal. However, during the 68 Ga-FAPI PET/CT examination, we observed significant radiotracer uptake along the iliopsoas muscle. This abnormal uptake pattern suggested potential biological activity in this specific area. Combined with physical examination, the patient was diagnosed with iliopsoas fibrosis.The presented images indicated that the uptake pattern was an important indicator for diagnosis, and the prospect of fibroblast activation protein in the diagnosis of skeletal muscle fibrosis has shown certain application value.